Ankle fractures: the operative outcome - Zulkifly, Ahmad Hafiz; Mohd Yusof, Nazri; Mohd Amin, Azril; N. A., Kassim; N., Nordin; S., Daraup; N., Premchandran (Malaysian Orthopaedic Association, 2011)
Ankle fractures are commonly seen in orthopaedic practice. This retrospective study of patients with ankle fractures who underwent surgical treatment in our institution from January 2000 to December 2003 was undertaken to analyze the common causes and patterns of ankle fractures; and the functional outcome of operative treatment for these fractures. Eighty patients were identified and reviewed. There were 65 male (81.3%) and 15 female patients (18.7%) with age ranging from 13 to 71 years old (mean, 32.3y). Common causes of ankle fractures were trauma (especially motor vehicle accidents), sports injuries and the osteoporotic bones in the elderly. Weber C (64.0%) was the most common pattern of fracture at presentation. The most common operative treatment for ankle fractures was open reduction and internal fixation (73 patients, 91.2%). Excellent and good outcomes were achieved in 93.8% of cases when measured using the Olerud and Molander scoring system for foot and ankle. In conclusion, operative treatment for ankle fractures restores sufficient stability and allowed mobility of the ankle joint.